Squidding around. 1, Fish feud - Sherry, Kevin (Squidding around, 2020)
Squizzard is a small squid who always wants to be the center of attention, whether it is playing with his best friend Toothy the vegetarian Great White Shark, or giving a report in school; but when his behavior finally causes a rift in their friendship, Shay the seahorse explains what he is doing wrong--but change is difficult for Squizzard and it takes an ecounter with Bennie the Barracuda, the fifth-grade bully at Deep Reef Elementary, to finally teach him the error of his ways.